The making and keeping of a home - Carleton, Margaret Isaphene (My University, 1896)
Introduction: Home has been defined as, “A centre midst a busy and weary world, for friendship, low and repose.” But many there are to whom no such a retreat is opened. A man may own a beautiful residence, furnished in all modern elegance, yet be without a home. Home must be a place filled with love, peace and rest. And it must be presided over by one who has the artistic power to make it such. For those, who under all circumstances have the genius and tact necessary to make a true home, are to be considered the world’s greatest artists.
Citation: Carleton, Margaret Isaphene. The making and keeping of a home. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Home; Man; Love; Peace; Rest; Theses; Manuscripts (documents)